2009
DOI: 10.1002/ejlt.200900078
|View full text |Cite
|
Sign up to set email alerts
|

The application of biotechnological methods for the synthesis of biodiesel

Abstract: Synthesis of biodiesel is performed mainly by chemical catalysis, but can also be performed by enzymatic or microbial methods, and these might play an important role in future substitution of petroleum-based diesel. To discover sustainable, economically attractive biotechnological processes for biodiesel synthesis, close cooperation between different disciplines is needed. Currently, lipases are the enzymes of choice for the synthesis of fatty acid esters (FAE) from fats and oils, yielding biodiesel with the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
5

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 134 publications
0
55
0
5
Order By: Relevance
“…Besides the most obvious use of TAG as edible oils and fats, they have attracted a great and increasing interest for use in the production of fuels such as biodiesel (fatty acid alkyl esters [FAAE]) consisting of TAG-derived fatty acids esterified with short-chain alcohols (mainly methanol) as substitutes for diesel fuel (36). Furthermore, TAG are used as additives for a variety of therapeutic or pharmaceutical purposes.…”
Section: Biotechnological Relevance Of Tag and Wementioning
confidence: 99%
“…Besides the most obvious use of TAG as edible oils and fats, they have attracted a great and increasing interest for use in the production of fuels such as biodiesel (fatty acid alkyl esters [FAAE]) consisting of TAG-derived fatty acids esterified with short-chain alcohols (mainly methanol) as substitutes for diesel fuel (36). Furthermore, TAG are used as additives for a variety of therapeutic or pharmaceutical purposes.…”
Section: Biotechnological Relevance Of Tag and Wementioning
confidence: 99%
“…This methodology avoids the separation of glycerol before its transformation and, in a similar way as previously obtained with derivatives of glycerol [17][18][19], these biofuels not only prevent the generation of waste, but also increase the yields of the process, always higher than nominal 10%, by incorporating some derivatives of glycerol into the reaction products. Novel methodologies to prepare esters from lipids using different acyl acceptors which directly afford alternative co-products are currently under development [13,[20][21][22]. The transesterification reaction of triglycerides with dimethyl carbonate (DMC) [23][24][25][26][27], methyl acetate [28][29][30][31][32] or ethyl acetate [33,34] can generate a mixture of three FAME or FAEE molecules and one of glycerol carbonate (GC) or glycerol triacetate (triacetin).…”
Section: Introductionmentioning
confidence: 99%
“…As in the two methods described before [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], the already patented Ecodiesel-100 [37][38][39] obtained through the 1,3-selective partial ethanolysis of the triglycerides with PPL, is a mixture of two parts of FAEE and one part of MG, that integrates the glycerol as a soluble derivative product (MG) in the diesel fuel, but unlike these methods, no specific reagent (such as dimethyl carbonate or methyl acetate) more expensive than methanol (or ethanol) are used. This strategy is based on obtaining an incomplete alcoholysis by application of 1,3-selective lipases, so that the glycerol remains in the form of monoglyceride which avoids the production of glycerol as a by-product, reducing the environmental impact of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, it has also been suggested as a potential feedstock for biodiesel industry (Adamczak et al, 2009;Easterling et al, 2009;Li et al, 2008;Vicente et al, 2010), because microbial lipid can be produced using various cheap feedstocks, especially renewable biomaterials such as lignocelluloses. Early studies suggested that oleaginous microorganisms should be cultivated for lipid accumulation in the media with excess carbon sources and one particular limiting element such as nitrogen, phosphorus, zinc, iron or magnesium (Gill et al, 1977;Jakobsen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%